2011
DOI: 10.1097/nmd.0b013e31821cd28a
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Alliance and Technique in Predicting Patient Outcome During Psychodynamic Psychotherapy

Abstract: The current study examined whether alliance interacted with psychodynamic interventions to predict patients' psychotherapy outcomes. A prospective study of psychodynamic psychotherapy with 68 outpatients who were treated by 23 therapists was used. The patients rated the alliance with their therapist early in treatment. Therapist use of psychodynamic techniques was reliably rated by independent clinicians for the same sessions. The therapy outcomes were measured at the end of treatment based on the patients' gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
81
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 34 publications
4
81
0
3
Order By: Relevance
“…Some researchers have productively explored the interaction of dynamic techniques and therapeutic alliance in predicting outcome (e.g., Barber et al, 2008;Gaston et al, 1998;Høglend et al, 2011;Owen & Hilsenroth, 2011). Others have examined how competent delivery of dynamic techniques relates to symptom change (e.g., .…”
mentioning
confidence: 98%
“…Some researchers have productively explored the interaction of dynamic techniques and therapeutic alliance in predicting outcome (e.g., Barber et al, 2008;Gaston et al, 1998;Høglend et al, 2011;Owen & Hilsenroth, 2011). Others have examined how competent delivery of dynamic techniques relates to symptom change (e.g., .…”
mentioning
confidence: 98%
“…Our findings in no way suggest that clients' perceptions of their counselors' cultural competencies are not important. Indeed, previous studies, including those with mainly Asian American client samples, have demonstrated that clients' perceptions of their counselors' cultural orientation are associated with better therapy outcomes (e.g., Owen, Leach et al, ; Owen, Tao et al, ). Rather, this study was aimed at understanding whether specific therapeutic factors may be endorsed more favorably by Asian Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Although a lot of attention has been commensurate with this idea, there is still literature that identifies effective counseling practice as consisting of specific interventions and therapeutic processes. Such suggestions are tantamount to promoting stereotypes and could contribute to microaggressions in therapy (Constantine, ; Owen, Imel et al, ). Although more research is needed to strongly assert one way or another about the evidence base for culturally specific interventions, our research suggests that there are no significant differences in helpful interactions and, as such, there is no reason to believe that implementing culturally adapted treatments with Asian American clients will reduce mental health disparities.…”
Section: Discussionmentioning
confidence: 99%
“…These results imply that an engaged therapist, who reviews the problems to be addressed and participates actively in the change process, is viewed by patients as most helpful. Owen and Hilsenroth (2011) demonstrated that patient-rated alliance in the psychodynamic treatment of 68 outpatients was significantly related to improvement on a measure of broad functioning. Specific psychodynamic techniques, including linking current feelings or perceptions to those from the past, focusing on repetitive relational patterns over time, and identifying recurrent patterns in the patient's actions, feelings, and experiences, were all found to enhance alliance in ways that improved outcome (Owen & Hilsenroth, 2011).…”
Section: Therapeutic Strategy Technical Skill and Therapist Actionmentioning
confidence: 98%
“…Owen and Hilsenroth (2011) demonstrated that patient-rated alliance in the psychodynamic treatment of 68 outpatients was significantly related to improvement on a measure of broad functioning. Specific psychodynamic techniques, including linking current feelings or perceptions to those from the past, focusing on repetitive relational patterns over time, and identifying recurrent patterns in the patient's actions, feelings, and experiences, were all found to enhance alliance in ways that improved outcome (Owen & Hilsenroth, 2011). In another study by this same team (Owen, Hilsenroth, & Rodolfa, 2012), alliance measures from both cognitive-behavioral and psychodynamic treatments were obtained and compared, leading the authors to conclude that the specific and active psychodynamic techniques utilized in both groups were associated with postsession change.…”
Section: Therapeutic Strategy Technical Skill and Therapist Actionmentioning
confidence: 98%